2018
DOI: 10.3390/foods7060088
|View full text |Cite
|
Sign up to set email alerts
|

Protection by the Total Flavonoids from Rosa laevigata Michx Fruit against Lipopolysaccharide-Induced Liver Injury in Mice via Modulation of FXR Signaling

Abstract: We previously reported the effects of the total flavonoids (TFs) from Rosa laevigata Michx fruit against carbon tetrachloride-induced liver damage, non-alcoholic fatty liver disease, and liver ischemia-reperfusion injury. However, there have been no papers reporting the role of R. laevigata TFs against lipopolysaccharide (LPS)-induced liver injury. In this paper, liver injury in mice was induced by LPS, and R. Laevigata extract was intragastrically administered to the mice for 7 days. Biochemical parameters in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 47 publications
(54 reference statements)
1
20
1
Order By: Relevance
“…Guo et al (2013) also report that the addition of lotus leaf extract to the diet increased the mRNA levels of genes involved in fatty acid β-oxidation in the liver of hamsters as observed in the present study. Other flavonoid-rich plant extracts also show similar regulation of lipid catabolism (Liu et al, 2017;Dong et al, 2018). These results indicate that AELL, like other flavonoid-rich plant extracts, have positive effects on lipid catabolism through enhancement of fatty acid β-oxidation.…”
Section: Discussionmentioning
confidence: 60%
“…Guo et al (2013) also report that the addition of lotus leaf extract to the diet increased the mRNA levels of genes involved in fatty acid β-oxidation in the liver of hamsters as observed in the present study. Other flavonoid-rich plant extracts also show similar regulation of lipid catabolism (Liu et al, 2017;Dong et al, 2018). These results indicate that AELL, like other flavonoid-rich plant extracts, have positive effects on lipid catabolism through enhancement of fatty acid β-oxidation.…”
Section: Discussionmentioning
confidence: 60%
“…Similarly, Dong et al. (2018) indicated that total flavonoids from Rosa laevigata Michx Fruit could exert a hypolipidemic role in liver injury induced by toxicant through modulating FXR/SREBP‐1c pathway. They suggested that total flavonoids had an inhibitory effect on lipopolysaccharides‐induced lipid accumulation in the liver by up‐regulating FXR and decreasing the levels of SREBP‐1c and FAS (Dong et al., 2018).…”
Section: Discussionmentioning
confidence: 96%
“…(2018) indicated that total flavonoids from Rosa laevigata Michx Fruit could exert a hypolipidemic role in liver injury induced by toxicant through modulating FXR/SREBP‐1c pathway. They suggested that total flavonoids had an inhibitory effect on lipopolysaccharides‐induced lipid accumulation in the liver by up‐regulating FXR and decreasing the levels of SREBP‐1c and FAS (Dong et al., 2018). Since the protective role of FXR against lipid accumulation is linked to the suppression of SREBP‐1c‐mediated lipogenesis (Watanabe et al., 2004; Zhang, Castellani, Sinal, Gonzalez, & Edwards, 2004), it seems that trans ‐chalcone can protect the kidneys of rats against HFD‐induced renal disease through the modulation of FXR/SREBP‐1c/FAS pathway.…”
Section: Discussionmentioning
confidence: 99%
“…ALI is a life-threatening disease with high morbidity and mortality rates. Endotoxin-induced hepatotoxicity remains a major source of death [55]. The liver index was usually used to assess liver damage in animal experiments [56].…”
Section: Discussionmentioning
confidence: 99%